2001
DOI: 10.1002/1521-396x(200106)185:2<247::aid-pssa247>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of Ultrasonic Waves in Bulk GaN and GaAlN/GaN Heterostructures

Abstract: We report the results of calculations of ultrasonic amplification in bulk and 2D GaN, as a function of both ultrasound frequency and electron drift velocity. It is shown that GaN is in principle, a suitable material for the observation of acoustoelectric gain at applied fields corresponding to electron drift velocities, which are slightly higher than the sound velocity. As a result, acoustoelectric instabilities should prevail before the onset of other nonlinear effects associated with hot electron transport. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Bulk GaN has an electron saturation velocity greater than 10 5 m/s, comfortably higher than the acoustic velocity by more than an order of magnitude 26 27 . Impact ionization effects are not expected till electric fields of at least 150 MV/m 28 , enabling large values of η before velocity saturation or breakdown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bulk GaN has an electron saturation velocity greater than 10 5 m/s, comfortably higher than the acoustic velocity by more than an order of magnitude 26 27 . Impact ionization effects are not expected till electric fields of at least 150 MV/m 28 , enabling large values of η before velocity saturation or breakdown.…”
Section: Resultsmentioning
confidence: 99%
“…This dynamic and reversible improvement in the Q of PS-BAW resonators can be distinctly observed on applying a DC electric field. Experimental work presented here has focused on GaN as it is a high-quality acoustic PS material predicted to be optimal for demonstrating acoustoelectric amplification 28 33 . Measured results presented here verify these predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts have been made to evaluate the viability of achieving acoustoelectric amplification in bulk GaN. Significant among these recent analyses is the work by Abdelraheem et al [9] and Mensah et al [10] who analytically demonstrated that GaN is a suitable material for the observation of acoustoelectric gain.…”
Section: Acoustoelectric Amplificationmentioning
confidence: 99%